Assessment of Lean Construction Principles: A Case Study at Semarang Medical Centre Hospital Project - Roy Adi Wijaya, Matias; Utomo Dwi Hatmoko, Jati; Suripin, Suripin (Department of Civil Engineering, Diponegoro University, 2015)
The lean construction frameworks have been developed for years to enhance the poor performance of Indonesian project delivery system which influenced by the waste of non-value adding activities. Never the less most of the developments were limited on working process and lack in people empowerment. Toyota Way which integrate working process optimization and people empowerment, was developed as a lean construction frame works. This paper aimed to assess the implementation of Toyota Way principles in project delivery system by observing project’s delivery current state (status quo). The assessment began by conducting a questionnaire survey about Toyota Way implementation which then validated by interview with involved stakeholders and field observation. The assessment showed that project’s stakeholders were still unfamiliar with Toyota Way concept. Although some Toyota Way guidelines have been used in projects completion process such as visual management and training program, it found that those guidelines had not fully implemented. The project delivery system was lack of process focus and concerns more on relationship inter-parties. It also found thatToyota Way implementation will constrained by the difficulties to change the status quo of project delivery. Moreover, it seems that construction projects need practical guidelines to simplify the Toyota Way implementation in project delivery system such as project flow evaluation and system of reflection.